The politically incorrect: The morbid art of auditory perversion. (The Voz a Vos Bulletin, 2026)
This article reflects on the configuration of the category of "perversion" not as an intrinsic quality, but as a sociocultural and historical mechanism intended to delimit the boundaries between the normative and the forbidden. Through an interdisciplinary review that encompasses anthropology, sociology, and psychoanalysis, he examines how what is called perverse acquires a symbolic power that becomes morbid: a collective fascination and an insatiable curiosity for the transgressor.This research is central to the aesthetic experience of radio dramaturgy, "Perverse stories - morbid ears". This work proposes a shift from ocularcentrism - the hegemony of gaze in the Western tradition - to purely auditory immersion. Sound theater is here constituted as a political and pedagogical device that invites the viewer to confront the morally ambiguous.
Keywords: Pervertion; Disease; Radial dramaturgy; Active listening; Transgression